Analisis Yuridis Terhadap Putusan Badan Arbitrase Nasional Indonesia Yang di Tolak Oleh Pengadilan Negeri Untuk di Eksekusi - Rina Shahriyani Shahrullah; Wagiman Wagiman; Yovita Yovita (Fakultas Hukum, Universitas Internasional Batam, 2015)
Law No. 30 of 1999 about Arbitration and Alternative Dispute Resolution set on the cancellation of the arbitral decision on Article 70 which said the parties may apply for cancellation if the arbitration decision is thought contain elements of forgery / document, or discovered hidden documents from opposing party, or a decision which taken on the results ruse by one of the parties in the dispute. The cancellation reason on this article must be evidenced by the court. However, on the practice the cancellation of arbitration decision by District Court still was not click with the law and inconsistent, especially related with the using reasons of cancellation in Article 70 Law No. 30 of 1999.The problems that would be discussed were (1) how was the juridical approachment that been done by BANI for making decision No.300/II/ARB-BANI-2009 that been cancelled by South Jakarta District Court, and (2) why South Jakarta District Court refused to execute BANI decision No.300/II/ARB-BANI-2009. This research was using normative juridical methode, which this research was focused to reviewing the application or the rules or norms of the positive law.Based on the research, South Jakarta District Court was wrong by expand decision No. 270/Pdt.P/2009/PN.Jkt.Sel, because on the decision by Panels of Judges on cancelling one decision was not based on Article 70 Law No. 30 of 1999 about Arbitration and Alternative Dispute Resolution. In fact, the only Article that arrange about cancel the arbitration decision just only on Article 70 in that Law.The implementation Article 54 and 57 Law No. 30 of 1999 about Arbitration and Alternative Dispute Resolution can not be the basis of cancellation request arbitration decision No. 300/II/ARB-BANI/2009 by Panel of Judges in South Jakarta.